2002
DOI: 10.1007/s00280-001-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paclitaxel, cyclophosphamide, ifosfamide, tamoxifen and cyclosporine on the metabolism of methoxymorpholinodoxorubicin in human liver microsomes

Abstract: The effects of paclitaxel, cyclosporine, cyclophosphamide, ifosfamide and tamoxifen on the metabolism of methoxymorpholinodoxorubicin (MMDx), a novel anticancer agent, were investigated using human liver microsomes. Paclitaxel, tamoxifen and cyclosporine dramatically inhibited MMDx metabolism, whereas ifosfamide had only a slight effect at high concentrations (200-300 microM) and cyclophosphamide had no effect. The inhibition was dependent on the concentrations of both MMDx and the coincubated drug. Thus, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These findings were extended by the present study, which revealed a strong correlation between CYP3A-catalyzed testosterone 6␤-hydroxylase activity and the potentiation of MMDX cytotoxicity in a panel of human liver microsomes and demonstrated that the human enzyme CYP3A4 and its rodent counterparts CYP3A1 and CYP3A2 are active catalysts of the prodrug activation reaction. These findings are consistent with the observation that the metabolism of MMDX by human liver microsomes can be competitively inhibited by the CYP3A4 substrates paclitaxel, tamoxifen, and cyclosporin (Beulz-Riche et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…These findings were extended by the present study, which revealed a strong correlation between CYP3A-catalyzed testosterone 6␤-hydroxylase activity and the potentiation of MMDX cytotoxicity in a panel of human liver microsomes and demonstrated that the human enzyme CYP3A4 and its rodent counterparts CYP3A1 and CYP3A2 are active catalysts of the prodrug activation reaction. These findings are consistent with the observation that the metabolism of MMDX by human liver microsomes can be competitively inhibited by the CYP3A4 substrates paclitaxel, tamoxifen, and cyclosporin (Beulz-Riche et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…PTX exhibited not only strong cytotoxic activities against the growth of human cervical cancer cell line HeLa cells at nanomolar concentrations but also cell-cycle arrest in the mitotic (M) phase without disturbing the synthesis (S) phase [ 19 , 20 ]. PTX has been demonstrated as an effective anticancer agent against lung, breast, ovarian, leukopenia, and liver cancer in various studies [ 21 , 22 , 23 , 24 , 25 , 26 ]. Thus, PTX was approved by the FDA in 1992 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AUC of paclitaxel was increased by 1.2 (1.1-1.4) by the combination. Paclitaxel had been reported as a CYP3A4 substrate (Beulz-Riche et al 2002). These pharmacokinetic data suggest that paclitaxel may act as an inhibitor of CYP3A4.…”
Section: Potential Drug Interactionsmentioning
confidence: 83%